Recognizing Green Skills Through Non-formal Learning A Comparative Study in Asia - Pavlova, Margarita; Singh, Madhu (Education for Sustainability, 2022)
This open access book looks into the roles and practices of small and micro-enterprises in formal and informal economies across seven countries and one territory in terms of how they contribute to environmental and sustainable development and green skills promotion. By taking into account the perspectives in these four sectors, catering, automotive, waste management and polyvinyl chloride production, this book maps environmental green practices in the region, identifying mechanisms used to assess existing skills (i.e. knowledge, skills and competencies), and evaluating the potential for green skills inclusion in recognition, validation and accreditation.